2022
DOI: 10.1039/d2ra03907a
|View full text |Cite
|
Sign up to set email alerts
|

A computational protocol for the calculation of the standard reduction potential of iron complexes: application to Fe2+/3+-Aβ model systems relevant to Alzheimer's disease

Abstract: Iron complexes play a key role in the development of neurological disorders, such as Alzheimer's disease. We provide a computational protocol based on DFT for the calculation of standard reduction potentials of iron complexes relevant to Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…In addition, iron slows down the aggregation process by preventing the orderly arrangement of the peptide, which is thought to increase its toxicity, and by its deposition along with the plaques, it creates new redox active sites that increase oxidative stress . This increase is supported by computational studies, which show that the complexes formed with Aβ have a reduction potential about 0.5 V lower than that of free iron under physiological conditions, increasing its reducing activity. , On the other hand, other studies suggest that this mechanism could be beneficial. An in vitro study showed that Pb 2+ and Pb 4+ intoxication inhibits APP translation in neurons, which produced a toxic accumulation of iron in the cytosol, but when iron was added to the medium, APP production was stimulated and then toxicity decreased.…”
Section: Metal Ions In Admentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, iron slows down the aggregation process by preventing the orderly arrangement of the peptide, which is thought to increase its toxicity, and by its deposition along with the plaques, it creates new redox active sites that increase oxidative stress . This increase is supported by computational studies, which show that the complexes formed with Aβ have a reduction potential about 0.5 V lower than that of free iron under physiological conditions, increasing its reducing activity. , On the other hand, other studies suggest that this mechanism could be beneficial. An in vitro study showed that Pb 2+ and Pb 4+ intoxication inhibits APP translation in neurons, which produced a toxic accumulation of iron in the cytosol, but when iron was added to the medium, APP production was stimulated and then toxicity decreased.…”
Section: Metal Ions In Admentioning
confidence: 99%
“…The inclusion of explicit solvent models has been shown to improve the calculation of the solvation free energy. However, this increases the computational cost considerably . According to the calculated SRP values, Fe-Aβ complexes could promote the catalytic production of hydrogen peroxide leading to an increase in the oxidative damage observed in AD brains.…”
Section: Metal Ions In Admentioning
confidence: 99%
See 1 more Smart Citation
“…These functionals and basis sets were chosen according to those that were used in publications regarding Fe 3 + , a detailed explanation of how these functionals and basis sets were chosen, is given below in section (a). The used functionals are the hybrid functional B3LYP that uses the non-local correlation, [16,17] the pure functional that uses gradient-corrected correlation PBE, [18] the functional BPW91 that is a combination of Becke exchange functional [16] (B) and the PW91 [19] correlational functional, the long-range corrected functional wB97X-D, [20] which includes empirical dispersion, and M06 L [21,22] that is a pure functional from the Truhlar group that is considered as very good for transition metals, [23] and the basis sets are TZVP [24] and the redefined Def2TZVP [25] of Ahlrichs and coworkers, aug-cc-pVTZ [26] that is a Dunning's correlation consistent basis set that includes diffuse functions, and 6-311 + + g(d,p) [27,28] that is a triple zeta all electron basis set that includes polarization and diffuse functions and is considered as very good for atoms of the two first rows of the periodic table. The SDD [29] basis set with effective core potential was used for Fe, while aug-cc-pVTZ and 6-311 + + g(d,p) were used for other atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Many benchmarking protocols have tried to decipher the best methodology for Ru metathesis as well as other transition metal catalysts compared either to experimental or theoretical observations (see for instance refs ). Herein, we will not provide a general answer for this conundrum.…”
Section: Introductionmentioning
confidence: 99%